2015
DOI: 10.1161/circgenetics.114.000598
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-150 Protects the Heart From Injury by Inhibiting Monocyte Accumulation in a Mouse Model of Acute Myocardial Infarction

Abstract: Background-MicroRNAs (miRs) and inflammatory monocytes participate in many cardiac pathophysiological processes including acute myocardial infarction (AMI). Recently, we observed that miR-150 is downregulated in injured mouse plasma after AMI as well as in human infarcted monocytes. However, the precise functional role of miR-150 in response to AMI remains unknown. Methods and Results-In a mouse model of AMI and in human subjects with AMI, we found that miR-150 expression was reduced in monocytes. In vitro stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
64
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(66 citation statements)
references
References 35 publications
0
64
2
Order By: Relevance
“…In a previous study, we found that plasma miR-150 levels were significantly associated with atrial fibrillation severity [23]. We also demonstrated that miR-150 disturbs the inflammatory response of peripheral blood monocytes in myocardial infarction by targeting CXCR4 [24]. These results suggest that miR-150 in peripheral blood can regulate the occurrence and development of cardiovascular diseases, such as myocardial infarction.…”
Section: Discussionmentioning
confidence: 66%
See 3 more Smart Citations
“…In a previous study, we found that plasma miR-150 levels were significantly associated with atrial fibrillation severity [23]. We also demonstrated that miR-150 disturbs the inflammatory response of peripheral blood monocytes in myocardial infarction by targeting CXCR4 [24]. These results suggest that miR-150 in peripheral blood can regulate the occurrence and development of cardiovascular diseases, such as myocardial infarction.…”
Section: Discussionmentioning
confidence: 66%
“…In our previous studies, we found that plasma miR-150 level was positively associated with atrial fibrillation severity [23]. We also observed that miR-150 regulates the migration of monocytes to the area of myocardial infarction by targeting CXCR4, thereby reducing the occurrence and development of myocardial fibrosis and protecting heart function [24]. These results suggest that miR-150 in peripheral blood can regulate the occurrence and development of cardiac fibrosis.…”
Section: Introductionmentioning
confidence: 73%
See 2 more Smart Citations
“…Specifically, miR-150 is predicted to target the inflammatory mediator IL-18 and is down-regulated in sepsis patients and following exposure of cells to bacterial lipopolysaccharide (LPS) in vitro (32, 33). Furthermore, Liu et al demonstrated miR-150 overexpression reduces inflammatory mediators (TNF-α, IL-1β, and IL-6) in monocytes (34). …”
Section: Introductionmentioning
confidence: 99%